Detecting gender bias in the coverage of politicians in Irish newspapers using automated text classification - Leavy, Susan (Trinity College (Dublin, Ireland). School of Computer Science & Statistics, 2014)
This thesis presents an investigation of whether there is evidence of gender bias in the coverage of politicians in Irish newspapers. Text-analysis techniques including natural language processing and machine learning are used to analyse newspaper content and highlighting differences in the coverage of male and female politicians. These differences are then analysed to identify any evidence of gender bias.
Keywords: Computer Science & Statistics, Ph.D.; Ph.D. Trinity College Dublin